The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41524-020-0305-x
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio theory of the negatively charged boron vacancy qubit in hexagonal boron nitride

Abstract: Highly correlated orbitals coupled with phonons in two-dimension are identified for paramagnetic and optically active boron vacancy in hexagonal boron nitride by first principles methods which are responsible for recently observed optically detected magnetic resonance signal. We report ab initio analysis of the correlated electronic structure of this center by density matrix renormalization group and Kohn-Sham density functional theory methods. By establishing the nature of the bright and dark states as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
234
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(282 citation statements)
references
References 39 publications
32
234
2
Order By: Relevance
“…We employ the CAM-B3LYP density functional [32][33][34] for this purpose, this calibrated, rangecorrected hybrid density functional being an example of an entrylevel method for the prediction of the spectroscopy of defects in molecular solids 24 . State energies reported by Ivády et al 31 are of the same order of magnitude as the present results, but some differ in basic nature to key ones identified herein. Firstprinciples-based approaches analogous to theirs are available that may prove useful for modelling defect spectroscopy [35][36][37][38][39] , but are not applied herein.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…We employ the CAM-B3LYP density functional [32][33][34] for this purpose, this calibrated, rangecorrected hybrid density functional being an example of an entrylevel method for the prediction of the spectroscopy of defects in molecular solids 24 . State energies reported by Ivády et al 31 are of the same order of magnitude as the present results, but some differ in basic nature to key ones identified herein. Firstprinciples-based approaches analogous to theirs are available that may prove useful for modelling defect spectroscopy [35][36][37][38][39] , but are not applied herein.…”
supporting
confidence: 71%
“…Calculations pertaining to the Gottscholl et al 16 ODMR observations have become available recently in the literature 31 . This also uses DFT to predict magnetic properties of bulk V À B defects, a critical novel conclusion being that strain-induced distortions away from full three-fold symmetry can interpret the observed off-axis ZFS parameter of E = 50 MHz.…”
mentioning
confidence: 99%
“…This means that the ground state of 2 B 2 is a static PJT system, and the ground state indeed exhibits low C s symmetry. We note here that strong electron-phonon interaction with membrane phonons play an important role in the activation of intersystem crossing process in boron-vacancy optically detected magnetic resonance center 49 . This type of phonon modes can be found only in 2D solid-state systems.…”
Section: Role Of Membrane Phononsmentioning
confidence: 75%
“…Prior to the detection of ODMR, no defect displaying photoluminescence had been assigned, only defects with observed magnetic properties [15,16]; defects exhibiting ODMR facilitate measurement of both the magnetic and photoluminescence properties. For one defect displaying ODMR [5], comparison of the observed magnetic properties to expectations [12] strongly suggested that the ODMR arises from the V − B defect (a charged boron vacancy), an interpretation that was quickly supported quantitatively [17,18]. Calculations have predicted that V − B has a triplet ground state [12,19], with a variety of low-energy triplet excited states predicted, within likely error limits, to have energies consistent with the observed photoemission energy [17,18].…”
Section: Introductionmentioning
confidence: 86%